2020
DOI: 10.1111/imj.15002
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin system inhibition and risk of infection and mortality in COVID‐19: a systematic review and meta‐analysis

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19, enters human cells by binding of its viral protein to the aminopeptidase angiotensin-converting enzyme 2 (ACE2). This has led to speculation whether treatment with renin-angiotensin system (RAS) inhibitors was associated with an increased likelihood of a positive test for COVID-19 and risk of mortality. Aims: We performed a systematic review and meta-analysis to investigate whether RAS inhibitors increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 44 publications
0
37
0
1
Order By: Relevance
“…New evidence since the publication of our original review includes results from a randomized controlled trial and 4 large database studies that included patients with a mix of disease severity ( 16–19 , 23 ). These studies consistently found that ACEI or ARB use was not associated with a higher risk for SARS-CoV-2 infection, findings which are further supported by 5 systematic reviews or meta-analyses ( 11 , 14 , 92–94 ). Because we consider these findings to be stable (meaning that future studies are likely to have the same results), we will no longer do literature surveillance on this KQ and will retire it from our living review.…”
Section: Key Question 1: Does the Use Of Aceis And Arbs Before Infectmentioning
confidence: 59%
See 1 more Smart Citation
“…New evidence since the publication of our original review includes results from a randomized controlled trial and 4 large database studies that included patients with a mix of disease severity ( 16–19 , 23 ). These studies consistently found that ACEI or ARB use was not associated with a higher risk for SARS-CoV-2 infection, findings which are further supported by 5 systematic reviews or meta-analyses ( 11 , 14 , 92–94 ). Because we consider these findings to be stable (meaning that future studies are likely to have the same results), we will no longer do literature surveillance on this KQ and will retire it from our living review.…”
Section: Key Question 1: Does the Use Of Aceis And Arbs Before Infectmentioning
confidence: 59%
“…These studies are all relevant to key question (KQ) 2 about the association of angiotensin-converting enzyme inhibitor (ACEI) or angiotensin-receptor blocker (ARB) use and coronavirus disease 2019 (COVID-19) severity, and they support our prior conclusion that ACEI or ARB use is not associated with a higher risk for severe COVID-19 illness. Two systematic reviews also address KQ1, adding support to our prior conclusion that ACEI or ARB use is not associated with an increased risk for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection ( 11 , 14 ).…”
mentioning
confidence: 73%
“…D allele of ACE I/D polymorphism mediates higher ACE expression) [10] and have been associated with acute respiratory distress syndrome (ARDS), hypertension, obesity/metabolic syndrome, cardiovascular risk, and abnormal blood clotting tendency; all of which represent clinical hallmarks of severe COVID-19 disease [reviewed in [4,11]]. In contrast, no clinical advantage was observed in COVID-19 patients treated with ACE inhibitors or angiotension receptor blockers (mediating high ACE2 and low angiotension II) [12], suggesting that further efforts are needed to fully comprehend the role of RAAS in COVID-19. Therefore, the present study employed an ecological meta-regression design to evaluate the ACE1 I/D genotypic data in relation to the observed differences in COVID- 19 inhabitants), GDP/capita (PPP), current health expenditure/capita (PPP), healthy life expectancy at birth, DALY diabetes mellitus, DALY hypertensive heart disease and DALY respiratory infections as retrieved from the World Health Organization website www.who.int/countries/en/.…”
Section: Introductionmentioning
confidence: 99%
“…Stopping the use of ARBs was recommended in the early phase of the pandemic due to the concern over possible increase in viral load [28, 29]. Recent studies have revealed safety of ARBs in patients with COVID-19 [30, 31]. Importantly, a recent study proposed that Losartan, an ARB, could ameliorate complications, especially of acute respiratory distress syndrome (ARDS) associated with COVID-19 [27].…”
Section: Introductionmentioning
confidence: 99%